Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium. Issue 1 (December 2018) - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Plötz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif; Asadollahi, Reza; et al.
Abstract Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.